![image](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7B6x%2B7%3E0%7D+%5Catop+%7B6x%2B7%3D7%5E%7B4%7D%7D%7D+%5Cright.+)
0} \atop {6x+7=7^{4}}} \right. " alt=" \left \{ {{6x+7>0} \atop {6x+7=7^{4}}} \right. " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Bx%3E-%5Cfrac%7B7%7D%7B6%7D+%7D+%5Catop+%7B6x%3D7%5E%7B4%7D-7%7D%7D+%5Cright.+)
-\frac{7}{6} } \atop {6x=7^{4}-7}} \right. " alt=" \left \{ {{x>-\frac{7}{6} } \atop {6x=7^{4}-7}} \right. " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Bx%3E-%5Cfrac%7B7%7D%7B6%7D+%7D+%5Catop+%7Bx%3D%5Cfrac%7B7%7D%7B6%7D%2A%287%5E%7B3%7D-1%29%7D%7D+%5Cright.+)
-\frac{7}{6} } \atop {x=\frac{7}{6}*(7^{3}-1)}} \right. " alt=" \left \{ {{x>-\frac{7}{6} } \atop {x=\frac{7}{6}*(7^{3}-1)}} \right. " align="absmiddle" class="latex-formula">
![x=\frac{7*342}{6}=7*57=399 x=\frac{7*342}{6}=7*57=399](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B7%2A342%7D%7B6%7D%3D7%2A57%3D399)
-
ответ
Проверка:
![2^{log_{16}(6*399+7)}=2^{log_{16}(2401)}=2^{log_{2}(\sqrt[4]{2401})}=\sqrt[4]{2401}=7 2^{log_{16}(6*399+7)}=2^{log_{16}(2401)}=2^{log_{2}(\sqrt[4]{2401})}=\sqrt[4]{2401}=7](https://tex.z-dn.net/?f=2%5E%7Blog_%7B16%7D%286%2A399%2B7%29%7D%3D2%5E%7Blog_%7B16%7D%282401%29%7D%3D2%5E%7Blog_%7B2%7D%28%5Csqrt%5B4%5D%7B2401%7D%29%7D%3D%5Csqrt%5B4%5D%7B2401%7D%3D7)
-
верно
Ответ: x=399